Global Myocardial Strain in Multisystem Inflammatory Syndrome in Children, Kawasaki Disease, and Healthy Children: A Network Meta-Analysis - Liu, Kaiwei; Yu, Jiahui; Song, Guang (Frontiers in Pediatrics, 2022)
Background: Nearly 6000 multisystem inflammatory syndrome in children (MIS-C) have been reported in the USA by November 2021. Left ventricular global myocardial strain has been proved to be one of the best evidence on the diagnostic and prognostic implications for cardiac dysfunction. The global myocardial strain change of MIS-C in the acute phase was still unclear. Methods: PubMed and other sources were searched. A network meta-analysis was conducted. MIS-C was divided into 2 groups according to left ventricular ejection fraction (LVEF): MIS-C with depressed ejection fraction (MIS-C dEF) and MIS-C with preserved ejection fraction (MIS-C pEF). Global longitudinal strain (GLS) and global circumferential strain (GCS) were compared among MIS-C, Kawasaki disease (KD), and healthy children. Results: Nine case-control studies were included, published between 2014 and 2021. These studies involved 107 MIS-C patients, 188 KD patients, and 356 healthy children. After Bayesian analysis, MIS-C dEF group was found to have a lower LVEF, higher GLS and GCS than KD groups. Both MIS-C pEF and KD had similar GLS and GCS, which were higher than healthy controls. There was no difference of LVEF among MIS-C pEF, KD, and healthy controls. Conclusions: MIS-C dEF was more severe than KD, both in LVEF and global myocardial strain. MIS-C pEF and KD were similar with mild impaired left ventricular myocardial strain, compared to the healthy children. Global myocardial strain may be a monitoring index for MIS-C.